2015
DOI: 10.1016/j.meteno.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic metabolic flux analysis using B-splines to study the effects of temperature shift on CHO cell metabolism

Abstract: a b s t r a c tMetabolic flux analysis (MFA) is widely used to estimate intracellular fluxes. Conventional MFA, however, is limited to continuous cultures and the mid-exponential growth phase of batch cultures. Dynamic MFA (DMFA) has emerged to characterize time-resolved metabolic fluxes for the entire culture period. Here, the linear DMFA approach was extended using B-spline fitting (B-DMFA) to estimate mass balanced fluxes. Smoother fits were achieved using reduced number of knots and parameters. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 55 publications
0
59
2
Order By: Relevance
“…It was also established in this study that the cell size increase is due to a proportional increase in biomass content (Table I), rather than due to a cell swelling effect through the uptake of water and salts. The cell DW measurement resulted in higher values (770 pg/cell or higher) than commonly reported for CHO cells (300-400 pg/cell) 57,85,86 . This can be explained by the larger cell size (17 µ m diameter on day 4) of the CHO cell line used in this study, compared to those reported (12-14 µ m diameter) 57 .…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…It was also established in this study that the cell size increase is due to a proportional increase in biomass content (Table I), rather than due to a cell swelling effect through the uptake of water and salts. The cell DW measurement resulted in higher values (770 pg/cell or higher) than commonly reported for CHO cells (300-400 pg/cell) 57,85,86 . This can be explained by the larger cell size (17 µ m diameter on day 4) of the CHO cell line used in this study, compared to those reported (12-14 µ m diameter) 57 .…”
Section: Discussioncontrasting
confidence: 54%
“…The cell DW measurement resulted in higher values (770 pg/cell or higher) than commonly reported for CHO cells (300-400 pg/cell) 57,85,86 . This can be explained by the larger cell size (17 µ m diameter on day 4) of the CHO cell line used in this study, compared to those reported (12-14 µ m diameter) 57 . We applied the same DW measurement for another cell line with an average cell diameter of 14 µ m at a viability higher than 90%, which A B resulted in ~330 pg/cell (data not shown).…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations